Correlation of immune fitness with response to teclistamab in relapsed/refractory multiple myeloma in the MajesTEC-1 study - Cortes-Selva, Diana; Perova, Tatiana; Skerget, Sheri; Vishwamitra, Deeksha; Stein, Sarah; Boominathan, Rengasamy; Lau, Onsay; Calara-Nielsen, Karl; Davis, Cuc; Patel, Jaymala; Banerjee, Arnob; Stephenson, Tara; et al. (Blood, 2024)
Teclistamab, an off-the-shelf B-cell maturation antigen (BCMA) × CD3 bispecific antibody that mediates T-cell activation and subsequent lysis of BCMA-expressing myeloma cells, is approved for the treatment of patients with relapsed/refractory multiple myeloma (R/RMM). As a T-cell redirection therapy, clinical outcomes with teclistamab may be influenced by patient immune fitness and tumor antigen expression. We correlated tumor characteristics and baseline immune profiles with clinical response and disease burden in patients with R/RMM from the pivotal phase 1/2 MajesTEC-1 study, focusing on patients treated with 1.5 mg/kg of teclistamab (N = 165). Peripheral blood samples were collected at screening, and bone marrow samples were collected at screening and cycle 3. Better clinical outcomes to teclistamab correlated with higher baseline total T-cell counts in the periphery. In addition, responders (partial response or better) had a lower proportion of immunosuppressive regulatory T cells (Tregs), T cells expressing coinhibitory receptors (CD38, PD-1, and PD-1/TIM-3), and soluble BCMA and a T-cell profile suggestive of a more cytolytic potential, compared with nonresponders. Neither frequency of baseline bone marrow BCMA expression nor BCMA-receptor density was associated with clinical response to teclistamab. Improved progression-free survival was observed in patients with a lower frequency of T cells expressing exhaustion markers and immunosuppressive Tregs. Overall, response to teclistamab was associated with baseline immune fitness; nonresponders had immune profiles suggestive of immune suppression and T-cell dysfunction. These findings illustrate the importance of the contribution of the immune landscape to T-cell redirection therapy response. This trial was registered at www.ClinicalTrials.gov as #NCT03145181/NCT04557098.